2023
DOI: 10.1186/s12905-023-02261-y
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of temperature controlled dual-mode radiofrequency in women with vaginal laxity

Abstract: Objective Vaginal laxity could negatively influence women’s sexual function. This study aimed to explore the efficacy and safety of temperature controlled dual-mode (monopolar and bipolar) radiofrequency (RF) in women with vaginal laxity. Methods A total of 102 patients with vaginal laxity were treated with temperature-controlled RF. The present study implemented Vaginal Laxity Questionnaire (VLQ), Female Sexual Function Index (FSFI) questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Pessary and RF were found to have little effect on enhancing the contraction force of muscle fibers. They mainly play a physical support and fascia regeneration role in the treatment of cystocele, rather than playing a role by enhancing pelvic floor muscle strength ( 25 , 26 ). In fact, the results in this study showed that the 3 treatments improve cystocele through different mechanisms; this discrepancy prompts further exploration into the underlying mechanisms and factors influencing these distinct treatment outcomes, and it will be beneficial for the clinical significance or potential consequences of patient outcomes and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Pessary and RF were found to have little effect on enhancing the contraction force of muscle fibers. They mainly play a physical support and fascia regeneration role in the treatment of cystocele, rather than playing a role by enhancing pelvic floor muscle strength ( 25 , 26 ). In fact, the results in this study showed that the 3 treatments improve cystocele through different mechanisms; this discrepancy prompts further exploration into the underlying mechanisms and factors influencing these distinct treatment outcomes, and it will be beneficial for the clinical significance or potential consequences of patient outcomes and treatment strategies.…”
Section: Discussionmentioning
confidence: 99%